2006
DOI: 10.1002/adma.200601288
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Polyelectrolyte Gel Membranes

Abstract: In the past two decades, synthesis of responsive membranes with pores that could be opened and closed by changing chemical or physical properties of their environment has been the subject of many publications (see Ulbricht's work for a recent review). [1][2][3][4][5][6][7][8] In most studies the variable pore permeability was attained by the surface modification of commercial microfiltration membranes using polymers that expand or contract in response to external stimuli. Radiation-and plasma-induced graft pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
101
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 13 publications
(9 reference statements)
1
101
0
Order By: Relevance
“…Their applications for controlled surface wettability, [6,7] thin-films permeability, [8,9] catalysis, [10] and particularly for assembling modified electrodes, [11] used in switchable sensors, [12] fuel cells, [13] and memory units, [14] resulted in novel materials, devices, and systems. [15,16] Recent integration of signal-responsive materials, functionalized switchable interfaces and biocomputing systems processing biochemical information resulted in the novel concept of biochemically controlled ''smart'' materials with built-in Boolean logic.…”
mentioning
confidence: 99%
“…Their applications for controlled surface wettability, [6,7] thin-films permeability, [8,9] catalysis, [10] and particularly for assembling modified electrodes, [11] used in switchable sensors, [12] fuel cells, [13] and memory units, [14] resulted in novel materials, devices, and systems. [15,16] Recent integration of signal-responsive materials, functionalized switchable interfaces and biocomputing systems processing biochemical information resulted in the novel concept of biochemically controlled ''smart'' materials with built-in Boolean logic.…”
mentioning
confidence: 99%
“…The membrane preparation and the mechanism responsible for pore formation are described in detail in our previous papers. [29,30] It has been previously demonstrated that only one-fifth of the pyridine groups were involved in the crosslinking, while the remaining groups could serve as pH-responsive units. [30] Two different kinds of gold particles were associated with the gel material to enable optical detection of changes in its swelling degree induced by an external signal (pH): gold NPs dispersed throughout in the gel and a layer of gold islands prepared on a glass substrate.…”
mentioning
confidence: 99%
“…Thin films with well-controlled nanoscale porosity-most interesting from the point of view of practical applications-are primarily from the multiphase materials through the selective removal of one of the polymeric phases or a sacrificial colloidal component in hybrid films. Some researchers proposed self-assembly methods based on liquidliquid phase separation in multi-component solutions comprising a stimuli-responsive cross-linkable polymer and a pore-forming component [102][103][104]. The phase separation occurred during spin-cast deposition of polymeric films.…”
Section: A Nano-blend With the Nano-phase Removed For Controlled Poromentioning
confidence: 99%
“…The phase separation occurred during spin-cast deposition of polymeric films. Tokarev et al [102] used monovalent salt to disrupt a polyelectrolyte complex of two biopolymers (alginate and gelatin), thus triggering their phase separation in spin-cast films. Hydrogen bonding between two water-soluble polymers can be also used to delay phase separation, as was demonstrated for the system composed of alginate and poly(vinyl alcohol) (PVA) [104].…”
Section: A Nano-blend With the Nano-phase Removed For Controlled Poromentioning
confidence: 99%